GRAPHIC AND MEANING IN LOGO DESIGN - Victor ADIR; George ADIR; Tiberiu DOBRESCU (Journal of Industrial Design and Engineering Graphics)
To design a logo is a special work. It means creation, intelligence, use of colors, and of course, signs and symbols. It is about a visual personality and a signature of an entity. During the working process, a designer has to answer to a few questions, such as: What signs, symbols and colors have to be used? or What are the important things be design in a logo? What are the logos in the market about a same activity? To answer means to design it. The meaning comes mainly from graphics and that is why it is compulsory to pay attention to each detail. The paper talks about the connection between graphic and meaning which may create a corporate identity.